The Theory and Application of the Management Game Approach to Teaching Business Policy - Schrieber, Albert N. (Academy of Management Journal, 1958)
Presents information on a study which described a management game theory that emphasizes the dynamic character of business. Purpose and structure of the game; Description of the game; Features of the game; Conclusions.